Protótipo acolhe: aplicativo móvel para rastreamento do distress de profissionais da Enfermagem - Nogueira, Luiz Fernando Oliveira (2023)
Introduction: Covid-19 pandemic has worsened the psychological distress of front line health care workers, mainly those in the nursing work environment. Computer technology is part of everyday life for most people, and the so-called mobile application softwares ("APP") are tools that help users to process data, identify problems, perform and facilitate tasks. Objective: To present a prototype for a mobile application, called ACOLHE, in order to support health workers in relation to the tracking of their work lifestyle; being able to identify possible psychic suffering. Method: Applied research in the modality of technological development; implemented into two phases: mapping of needs and presentation of the APP prototype. In the development of the prototype, the methodology of Contextualized Instructional Design (DIC) was used, with five stages (analysis; design, development, implementation and evaluation). In this research, the DIC model was adapted to four stages: 1 - analysis (literature review about the psychic suffering of the nursing team in the pandemic, besides the uncertainties about the work after the pandemic); 2 - design (application of the design thinking tool, which evolved to the construction of the instrument based on the Quadriphasic Model of Stress Classification of Lipp, the Stress Control Training and the Theoretical Methodological Descriptive Model of Quality of Life at Work); 3- development (application of Canvas, graphic design platform, a tool to map the value proposition of the technological invention and afterwards, together with the graphic design professional, the selection of tools for the mobile application, the definition of the navigation structure and the planning of the environment configuration, outlining a structured prototype following an order by screens from the Marvel APP) and, 4 - implementation (from the stimulation of the ideas and creation of the prototype functionalities, the tools and technological resources were setup for application on the Internet and installation in the APP). Results: The prototype was named "ACOLHE", for inspiring psychological welcoming to the staff when in vulnerable emotional situations. The content was built in relation to self-assessment of lifestyle, integrating the social, affective, health, and professional pillars, using a Likert scale in the answers. Regarding the functionalities of the prototype, the cycles of registration, self-assessment process, and outcome of self-assessment were created to allow users to map their lifestyle, identify predisposition to psychic suffering, and choose or not to choose psychological support, besides providing interaction between users and managers. The communication between the APP and the server is encrypted "end-to end" in order to meet the standards of security and user privacy. Conclusion: ACOLHE has proven to be a digital and interactive technological resource of communication, which can be of considerable use in organizations, allowing the mapping of health problems, supporting to collaborators in the follow-up of disorders conditions and monitoring of treatment measures. In relation to the promotion and prevention of diseases, preventing or minimizing psychological suffering. It can also provide tools for people management to improve interventions and foster new research focused on the use of technologies.